A neighborhood-level potential health impact scoring tool to support local-level health impact assessments. Issue 3 (1st September 2020) - Prochaska, John D.; Buschmann, Robert N.; Jupiter, Daniel C.
ABSTRACT: Health Impact Assessments (HIAs) have quickly become a widely utilized tool for integrating health and health-related evidence and data into decision-making processes across a range of projects and policies. Integrating and utilizing a wide range of available data can be daunting. To support communities seeking to engage in health impact assessments, we developed the Neighborhood Potential Health Impact Score (NPHIS) methodology. We present the NPHIS method's four-step process, and how this process was applied to an HIA focusing on the rebuilding of public housing following a natural disaster. We discuss developing the boundary definition, selection and definition of indicators, calculation of the NPHIS, and interpretation and utilization of the scores. Findings were validated using feedback from a community stakeholder advisory board as well as through feedback collected from focus groups of community residents. NPHIS methodology has proven to be a useful resource in better understanding the complex sources of potential health impacts facing communities, and in being an evidence-based, data-driven resource for HIA decision-makers and their stakeholders in our specific application. Other groups seeking to integrate similar data into their decision-making processes could benefit from replicating the NPHIS in their efforts.